6j-3=48j+34

Simple and best practice solution for 6j-3=48j+34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6j-3=48j+34 equation:


Simplifying
6j + -3 = 48j + 34

Reorder the terms:
-3 + 6j = 48j + 34

Reorder the terms:
-3 + 6j = 34 + 48j

Solving
-3 + 6j = 34 + 48j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-48j' to each side of the equation.
-3 + 6j + -48j = 34 + 48j + -48j

Combine like terms: 6j + -48j = -42j
-3 + -42j = 34 + 48j + -48j

Combine like terms: 48j + -48j = 0
-3 + -42j = 34 + 0
-3 + -42j = 34

Add '3' to each side of the equation.
-3 + 3 + -42j = 34 + 3

Combine like terms: -3 + 3 = 0
0 + -42j = 34 + 3
-42j = 34 + 3

Combine like terms: 34 + 3 = 37
-42j = 37

Divide each side by '-42'.
j = -0.880952381

Simplifying
j = -0.880952381

See similar equations:

| 2-1.5n=3n+16 | | 4y+17=2y-41 | | g+18=116 | | x^2+4x+10=5x+30 | | 1/3y-2=5 | | y-7=40 | | -8(s+5)=20 | | 5h-8=6h+45 | | 72x^2+39=71 | | 3z+1=4z+5 | | 6p+32=14 | | 8n-25=15+5n+13n | | (8x-3y)+(9x-y)= | | c+-12=-14 | | 4z+3=8z+2 | | 7h-5=8h+3 | | 5w-17=13 | | 10h+6=8h-5 | | 5q-10=8q+3 | | 3=r/2 | | 7y-5=3y+19 | | 9z+3=1z+4 | | 3 = r2 | | 2x-(6x+2)=36 | | 43z+13=53z+20 | | -4=-0.6k | | 8=q+3 | | 1/2t-16=0 | | 12a-10=26 | | -1.75=-1.5b+b | | 54r-18=45r+17 | | h+115=-11.5 |

Equations solver categories